The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1038/sc.2013.112
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and age effects of secondary health conditions in individuals with spinal cord injury: a scoping review

Abstract: Study design: Scoping review. Objectives: To gain a better understanding of the prevalence, course and association with age of secondary health conditions in individuals with spinal cord injury (SCI). Setting: Seattle, Washington, USA. Methods: We performed searches of electronic databases for studies published from 1986-2011 that provided information regarding the prevalence, course or associations with age and duration of secondary health conditions in individuals with SCI. Results: Ninety-two studies were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
129
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(139 citation statements)
references
References 106 publications
6
129
4
Order By: Relevance
“…The list was developed by considering the current literature and by involving health providers who had cared for pregnant women with SCIs. 25 The questionnaire specifically asked about skin problems, bowel function, UTI frequency, mode of delivery, decubital ulcers, hospital admissions, alterations in medication, respiratory tract problems and changes in neurogenic lower urinary tract dysfunction symptoms.…”
Section: Data Collectionmentioning
confidence: 99%
“…The list was developed by considering the current literature and by involving health providers who had cared for pregnant women with SCIs. 25 The questionnaire specifically asked about skin problems, bowel function, UTI frequency, mode of delivery, decubital ulcers, hospital admissions, alterations in medication, respiratory tract problems and changes in neurogenic lower urinary tract dysfunction symptoms.…”
Section: Data Collectionmentioning
confidence: 99%
“…4 Many of these conditions consequently are managed with pharmacotherapy. A prospective study in Denmark that investigated medication use among 72 patients admitted with a spinal cord lesion found that medication consumption increased 3.29-fold relative to that before SCI.…”
Section: Introductionmentioning
confidence: 99%
“…8,25 Economic and politic factors, ethical considerations, vision of the institution and caregivers in the Swiss health-care system influence this rate, allowing patients an ongoing in-house treatment until closure. 7,22 Although occurrence of PU is often discussed as an indicator of worse outcome and discharge destination, 4,7 closure of HAPU did not change the discharge destination in our population.…”
Section: Time Until Occurrencementioning
confidence: 82%
“…12,22 Focussing on highest occurrence per patient-years, our orthopaedic SCI patients had more HAPUs in the immediate postoperative period than non-SCI patients (25% versus 5%) 14 and a similar rates after 5 days of surgery (66.7% versus 58%). 14 Even though surgery is of influence, not all patterns can be explained; for example, low incidences in patients admitted for deep PUs that were almost all surgically closed.…”
Section: Time Until Occurrencementioning
confidence: 99%
See 1 more Smart Citation